Cisco Networking Academy Program: second-year companion guide (Cisco Systems, 2001)
Cisco Networking Academy Program: Second Year Companion Guide, Second Edition is the revised and improve text companion to the third and fourth semesters of Cisco Networking Academy Program classes. This bestseller, supports and reinforces the on-line learning for the Academy, along with topics pertaining to CCNA certification. The second year of the curriculum deals with the practical application of networking concepts the book will include the following:Learning objectives that the readers will know after completing each chapterLabs that provide students with an active learning experience of network design and developmentThreaded Case studies that present students with the experience of network developers. These studies will run throughout the book and increase in difficulty, as the case study becomes more involved.Developed with and approved by Cisco Systems, Cisco Networking Academy Program: Second Year Companion Guide, Second Edition will provide information and presentation unmatchable by any other publisher.